Population‐based study of laparoscopic colorectal cancer surgery 2006–2008. Issue 4 (3rd January 2013) - Taylor, E. F.; Thomas, J. D.; Whitehouse, L. E.; Quirke, P.; Jayne, D.; Finan, P. J.; Forman, D.; Wilkinson, J. R.; Morris, E. J. A.
Abstract Background: Clinical guidelines recommend that, where clinically appropriate, laparoscopic tumour resections should be available for patients with colorectal cancer. This study aimed to examine the introduction of laparoscopic surgery in the English National Health Service. Methods: Data were extracted from the National Cancer Data Repository on all patients who underwent major resection for a primary colorectal cancer diagnosed between 2006 and 2008. Laparoscopic procedures were identified from codes in the Hospital Episode Statistics and National Bowel Cancer Audit Project data in the resource. Trends in the use of laparoscopic surgery and its influence on outcomes were examined. Results: Of 58 135 resections undertaken over the study period, 10 955 (18·8 per cent) were attempted laparoscopically. This increased from 10·0 (95 per cent confidence interval (c.i.) 8·1 to 12·0) per cent in 2006 to 28·4 (25·4 to 31·4) per cent in 2008. Laparoscopic surgery was used less in patients with advanced disease (modified Dukes' stage 'D' versus A: odds ratio (OR) 0·45, 95 per cent c.i. 0·40 to 0·50), rectal tumours (OR 0·71, 0·67 to 0·75), those with more co‐morbidity (Charlson score 3 or more versus 0: OR 0·69, 0·58 to 0·82) or presenting as an emergency (OR 0·15, 0·13 to 0·17). A total of 1652 laparoscopic procedures (15·1 per cent) were converted to open surgery. Conversion was more likely in advanced disease (modified Dukes' stage 'D' versus A: OR 1·56, 1·20 to 2·03), rectal tumours (OR 1·29, 1·14 to 1·46) and emergencies (OR 2·06, 1·54 to 2·76). Length of hospital stay (OR 0·65, 0·64 to 0·66), 30‐day postoperative mortality (OR 0·55, 0·48 to 0·64) and risk of death within 1 year (hazard ratio 0·60, 0·55 to 0·65) were reduced in the laparoscopic group. Conclusion: Laparoscopic surgery was used more frequently in low‐risk patients. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.